Eosinophilic asthma, according to a blood eosinophil criterion, is associated with disease severity and lack of control among underprivileged urban Brazilians. (December 2018) - Lima-Matos, Aline; Ponte, Eduardo Vieira; de Jesus, Juliana Pires Viana; Almeida, Paula Cristina Andrade; Lima, Valmar Bião; Kwon, Namhee; Riley, John; de Mello, Luane Marques; Cruz, Álvaro A.
Abstract: Background: Asthma is a syndrome with multiple phenotypes. Peripheral blood eosinophil counts might be the ideal biomarker to identify subjects with eosinophilic asthma. It is available, inexpensive, and it is associated with eosinophilia in sputum. Objective: The aim of this study was to evaluate whether blood eosinophilia is associated with asthma severity and to evaluate whether blood eosinophilia is associated with lack of control of asthma symptoms and airway obstruction. Methods: Case control study. The cases were subjects recruited from a cohort of patients with severe asthma, in Salvador-BR, demanding continuous inhaled corticosteroids and LABA. There were two control groups: 1) subjects with mild/moderate asthma, 2) subjects with no asthma. Subjects enrolled in the study answered questionnaires, had their blood and stool samples collected, performed spirometry and SPT. We established a cutoff ≥ 260 cells/mm3 for blood eosinophilia. Results: We evaluated 544 subjects in the case group, 452 subjects with mild to moderate asthma and 450 subjects with no asthma. The subjects of the case group had higher odds of presenting the eosinophilic phenotype in comparison to subjects with mild to moderate asthma [OR 1.60 95CI(1.19-2.16)] and no asthma [OR 3.93; 95CI(2.90-5.33)]. The eosinophilic phenotype, according to blood count, is associated with uncontrolled asthma [OR 1.56; 95CI(1.06-2.28)], but it is not associated with airway obstruction [OR 0.87; 95CI(0.61-1.24)]. Conclusion: We conclude that the blood eosinophilia is a biomarker associated with asthma severity and poor symptom control, but we found no association with reduced lung function. Highlights: Blood eosinophilia was associated with asthma severity and poor symptoms control. Blood eosinophilia was not associated with reduced lung function. Blood eosinophilia was not associated with the skin prick test to aeroallergens. Blood eosinophilia was associated with high total IgE in the serum.